Territory, glocalisation and territorialisation as development determinants - Łuczyszyn, Andrzej (Terytorium, glokalizacja i terytorializacja jako determinanty rozwoju, 2021)
At a time when the world economy is experiencing rapid changes, a new paradigm of development referred to as a territory-oriented approach is growing in importance. This shift in the general concept of development is driven by a multitude of factors, including in particular the fact that development is a historical product and as such it has its own temporal dimension. Both regional and local developments are dynamic models where constant interactions occur between local and global elements. These interactions create a system in which spatially concentrated and historically formed technical, productive and institutional activities are performed and coordinated in a variety of ways by all kinds of organizations, in other words a territory. One may argue that territories evolve and their history is made up of subsequent development stages and of new external situations which compel them to make continuous adjustments. Within their borders, there is an ongoing combination of development factors, with the territory’s differentiating features being unique and not easily replicable. As such, territories are specific social structures. Contemporary social realities require that local and regional dimensions be brought up together with the world – a global dimension. This makes territories a stage for economic actors.
Biblioteka Regionalisty, 2021, Nr 21, s. 78-91
Keywords: territory; glocalization; territorialisation; terytorium; glokalizacja; terytorializacja